ULTRASOUND GUIDED PERIPHERAL NERVE BLOCK FOR TRIGEMINAL NEURALGIA: A CASE REPORT - Bambang Sulistyo; Wisnu Budi Pramono (Mandala Of Health, 2026)
Background: Trigeminal neuralgia (TN), also known as tic douloureux, is a severe neuropathic pain disorder characterized by recurrent unilateral facial pain. Although pharmacological therapy remains the first-line treatment, a significant proportion of patients experience inadequate pain control or adverse effects. Alternative minimally invasive approaches are therefore needed. Case Presentation: A 26-year-old woman presented with a one-year history of severe, paroxysmal, electric shock-like pain on the left side of her face, with a Visual Analog Scale (VAS) score of 6. The pain was triggered by daily activities such as talking, eating, and brushing teeth. Clinical and laboratory examinations showed no abnormalities, and the patient was diagnosed with trigeminal neuralgia. Pharmacological treatment with paracetamol and pregabalin provided only temporary relief. The patient declined invasive procedures targeting the trigeminal ganglion. Intervention and Outcome: The patient underwent ultrasound-guided peripheral nerve block targeting the supraorbital, infraorbital, and mental nerves using lidocaine and dexamethasone. Immediately after the procedure, the patient reported complete pain relief (VAS score 0). At 7 days follow-up, the patient discontinued medication without recurrence of symptoms. At 3 months follow-up, the patient remained pain-free. Conclusion: Ultrasound-guided peripheral nerve block may serve as an effective and minimally invasive alternative for managing trigeminal neuralgia, particularly in patients who do not respond to pharmacological therapy or refuse more invasive procedures.